Rare seizure presentation in 3-year-old male: Case of focal epilepsy associated with squatting and running - Zayan Musa; Abhijnya Gowder; Herlinda Bergman; Roopa Viraraghavan (SAGE Open Medical Case Reports)
We report the case of a 3-year-old male initially observed to have breath-holding spells, squatting, and spontaneous crying who later developed symptoms of atypical seizures suggestive of focal epilepsy. Electroencephalogram confirmed focal seizures, while MRI revealed periventricular leukomalacia. Antiepileptic drugs were imperative to resolving the seizure symptoms, although complications arose with certain side effects. This case highlights the importance of identifying different characteristic seizure presentations and distinguishing breath-holding spells from atypical seizures through a timely electroencephalogram and neuroimaging to make an accurate diagnosis. In addition, we discuss the intricacy of diagnosing atypical seizures and the different ways in which they can present. Help the reader direct their attention to a valuable case report about childhood epilepsy and the uncommon symptoms associated. Highlighting the importance of identifying different characteristic seizure presentations and distinguishing breath-holding spells from atypical seizures through timely electroencephalogram and neuroimaging to make an accurate diagnosis.